Critically Dismantling the Myths of Social Studies Education - Santosa, Donald Samuel Slamet (Kirana Publisher (KNPub), 2024)
As time goes by, misunderstandings arise about what social sciences are and how social sciences (IPS) are applied in the world outside the classroom. This misunderstanding is so deeply rooted that it has become a myth. Myths have no basis in truth. Furthermore, myths serve not only to deceive but also to frustrate the beliefs of the founders of the progress of the human mind. Myths are generally associated with deceptive and dangerous illusions or discourses, which in reality have powerful and widespread power. Considering the dangers of myths (especially in Social Sciences Education) which can destroy the foundations of Social Sciences Education, this needs to be dismantled immediately. Critical reflective thinking is one of the best tools to start with. The aim of this study is: Identifying myths that develop in social studies education and dismantling selected social studies education myths through critical thinking/reflection. This research method is a literature review. The study was carried out based on 5 selected sources and analyzed with critical reflection. This research succeeded in identifying 17 things which were then summarized into 10 dangerous myths about social studies education using critical reflection. The implication is the need to provide socialization and implementation of new concepts related to Social Sciences Education to all stakeholders with the aim of forming new attitudes and positive support for Social Sciences Education. In particular, it is important to follow up on new ways of assessing social studies education, forming positive and productive attitudes and behavior in improving the quality of social studies education in the future.